Propagação in vitro e caracterização molecular de plantas do gênero Alternanthera - Rubin, Silvia (2007)
The plants are biologically important sources of natural actives products, many of the which are constituted in experimental models for the synthesis of new medicines. The genus Alternanthera is known by possessing plants with medicinal properties and are employed with this purpose for the popular medicine. Among they stand out A. dentata Moench., A. brasiliana L., A. tenella Colla and A. philoxeroides Mart., with diuretic properties, anti-inflammatory, digestive, hepatic-protector, antioxidant, analgesic, antibiotic, anti-tumor and depurifying effect. In the last years, it was verified an increase demand for medicinal plants and it is made necessary studies in relation to the morphologic, physiologic and molecular characteristics of these plants species. The objective of this study was to evaluate the micropropagation process, optimizing the cultivation in vitro system, and to verify the genetic similarity among the plants collected at different places of the South Area of Brazil. The basic procedures of micropropagação include the in vitro establishment, multiplication and aclimatization of the plantlets. In the micropropagation different BAP (0.0; 0.5; 1.0; 1.5; 2.0 and 2.5 mg L-1) and ANA (0.0 and 1,0 mg L-1) concentrations were used and growth parameters was evaluated. It was verified for Alternanthera dentate brasiliana that the best medium for the in vitro cultivation was MS medium without plant growth regulators and in the medium added of ANA (1.0 mg L-1), without the BAP addition. In these medium the plants developed sufficient to the acclimatization stage. The addition of 1,0 mg L-1 of ANA in the stage of in vitro cultivation improved the root system development during the aclimatização stage. The molecular analysis was conduced using the RAPD technique, in order to look for a possible polymorphisms among the genotypes of Alternanthera brasiliana and the potential of the technique in detecting variability intra and interespecific of A. dentata, A. philoxeroides, A. brasiliana, A. tenella, and A. sessilis plants harvesting at different places of the South Area of Brazil. Through the RAPD technique it was not possible to verify polymorphisms among the A. brasiliana plants and among the A. dentata ix plants. However, it was possible to differentiate the six different analyzed species and to observe variability among the plants of A. philoxeroides and A. tenella.